HORMONE PROFILE OF DISORDER OF SEX DEVELOPMENT (DSD) PATIENTS IN PALEMBANG - Maritska, Ziske; Prananjaya, Bintang Arroyantri; Parisa, Nita; Quardetta, Rovania Yantinez (Biomedical Journal of Indonesia, 2019)
Apart from being based on clinical findings, the determination of the diagnosis of Disorders of sex development (DSD) is also supported by a variety of supporting examinations such as chromosome analysis, radiology, and laboratory examinations, one of which is the examination of hormone levels. Examination of hormone levels can provide a picture of gonadal and adrenal function, which is useful both for screening and for determining the diagnosis of DSD. The study that aims to identify the hormone profile of DSD patients in Indonesia is still very minimal, and this study is the first study to review the profile of DSD hormones in RSUP Dr. Mohammad Hoesin Palembang. This study is a descriptive study using secondary data from the medical records of DSD patients who underwent hormonal examinations during the 2013-2017 period. Of the total 173 DSD patients who came for treatment at the Dr. Mohammad Hoesin Palembang during the last five years, only 22 (12.72%) patients underwent hormone testing. There were 13 hormone profiles that were examined in DSD patients at RSUP Dr. Mohammad Hoesin Palembang with the hormone testosterone (54.54%) as the most frequently examined hormone. Hormone profile examination as a screening aid and diagnosis of DSD has not become one of the most common supporting examinations carried out at Dr. RSUP. Mohammad Hoesin Palembang.